Modified pre-surgical technique for optimizing the mandibular deviation using gunning’s splint as discontinuity mandibulectomy prosthesis: A Case Report - Pavan Kumar Dubey; Rajesh Sethuraman (International Journal of Medical Research and Review, 2015)
Patients who have undergone mandibular resection are generally co-operative and philosophical in respect to their conditions. The prosthodontic prognosis is dependent on a number of complex factors. The extent of bony and soft tissue resection has significant impact. Patients with lateral discontinuity defects of the mandible have little hope of achieving pre-surgical levels of masticatory efficiency, however certain measures can be sought off to minimize the post surgical deviation. In this case report an effort has been made by incorporating the gunning’s splint with modified mechanism of interlocking in the form of mandibular discontinuity prosthesis with an intent to minimize the post surgical deviation